Lighthouse Chacachacare, Trinidad - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Photo of a lighthouse located in Chacachacare, off the north-west coast of Trinidad. There is a man standing outside the lighthouse. A hut and the roof of a flat building are also visible.
Colour: Sepia; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Lighthouses--Trinidad and Tobago; Islands--Trinidad and Tobago; Chacachacare--Trinidad and Tobago